Classroom Activities of Cooperative Learning in Chinese as a Foreign Language - Tiffany Qorie; Anas Ahmadi; Atiqoh Atiqoh (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
Chinese language as a foreign language class, teachers often use a collaborative learning model, one of the main characteristics is interpersonal interaction, when interacting with other people, students are required to use the Chinese language as the target language to communicate. The purpose of this research is to identify suitable classroom activities for cooperative learning in Chinese language classes. This research is a qualitative descriptive research. The data source is students from the Chinese Education Program of the State University of Surabaya basic level to advanced level students, data collection was carried out in a natural setting. Data collection techniques used are complete participant observation and interviews. Four cooperative learning activities are suitable for Chinese as a foreign language class, including 1) conversation cards, 2) role-play, 3) story-telling, and 4) debate. It is not only to improve communication and cooperation or collaborative skills between students, but another purpose is to grow students’ foreign language expression skills. Teachers should give students feedback by correcting pronunciation in each class activity.